Catatan atas Teologi Humanis Hasan Hanafi - Jarman Arroisi (Universitas Darussalam Gontor, 2014)
The paper explores, that the issue of humanism that carries the idea of man as central to all of life cannot seen as a simple idea. Moreover, Muslim scientists brought up the idea. That is not a few of Muslim scholars in various Islamic universities are working hard campaigning in support disseminated this idea. Humanism actually as understanding of what makes humans as the main shaft in life is unknown in Islamic tradition. This phenomenon needs to get an adequate answer, to give a true description of its concept. In addition, this paper also offers ideas that in order to achieve the betterment of life, a Muslim does not have to empty himself of religion and God. Otherwise, religion and God should not be forgotten. A Muslim has to examine Islam as soon, trough the discipline has been handed down by prophets, and which has been developed by previous scholars, diligently an earnestly, so as the explore of the old heritage, is it expect to find new original concept to answer nowadays problems.